2014
DOI: 10.4172/2157-7013.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific Estrogen Receptor Alpha Increases Angiogenesis,Lymphangiogenesis and Reduces Fibrosis in the Female Mouse Heart Post-Myocardial Infarction

Abstract: Experimental studies showed that 17β-estradiol (E2) and activated Estrogen Receptors (ER) protect the heart from ischemic injury. However, the underlying molecular mechanisms are not well understood. To investigate the role of ER-alpha (ERα) in cardiomyocytes in the setting of myocardial ischemia, we generated transgenic mice with cardiomyocyte-specific overexpression of ERα (ERα-OE) and subjected them to Myocardial Infarction (MI). At the basal level, female and male ERα-OE mice showed increased Left Ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 67 publications
3
36
0
1
Order By: Relevance
“…In this study, we observed ER-α expression to be significantly lower in senescent P30 fibroblasts and in the aged mice hearts than in corresponding P3 fibroblasts and young mice hearts, which suggest that the relationship between ER-α and ET-1 may be strategically important to aging-related cardiac fibrosis. A recent study indicated that ER-α expression in the female mouse hearts reduces cardiac fibrosis following myocardial ischemia [31]. The precise role of ER-α down-regulation in fibrosis in the aged hearts and in aging related cardiac dysfunction cannot be discerned from the present work.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we observed ER-α expression to be significantly lower in senescent P30 fibroblasts and in the aged mice hearts than in corresponding P3 fibroblasts and young mice hearts, which suggest that the relationship between ER-α and ET-1 may be strategically important to aging-related cardiac fibrosis. A recent study indicated that ER-α expression in the female mouse hearts reduces cardiac fibrosis following myocardial ischemia [31]. The precise role of ER-α down-regulation in fibrosis in the aged hearts and in aging related cardiac dysfunction cannot be discerned from the present work.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, the estrogen receptor (ER) beta versus ER-alpha receptor-mediated responses and the relative importance of genomic versus non-genomic effects are the subjects of considerable debate [43,47]. The cardioprotective role of E2 in the modulation of ischemia-reperfusion injury has been extensively investigated: in models, E2 acts at multiple cellular levels during ischemia-reperfusion, including cardiomyocytes and fibroblasts [46,[48][49][50][51].…”
Section: Mechanisms Responsible For Microvascular Dysfunction In Ischmentioning
confidence: 99%
“…Estrogen receptors are suggested to be important in various pathophysiologies, including cardiac dysfunctions (17,18). In clinic practice, estrogen treatment markedly improves myocardiac infarct size and heart failure (19). Previous studies have determined that ERs activate the downstream PI3K/Akt signaling pathway, thereby limiting the inflammatory responses in vivo and in vitro (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In clinic practice, estrogen treatment markedly improves myocardiac infarct size and heart failure (19). Previous studies have determined that ERs activate the downstream PI3K/Akt signaling pathway, thereby limiting the inflammatory responses in vivo and in vitro (19,20). As an RNA helicase, p72 binds to double and single stranded RNA.…”
Section: Discussionmentioning
confidence: 99%